Accurate identification and discrimination of Salmonella enterica serovar Gallinarum biovars Gallinarum and Pullorum by a multiplex PCR based on the new genes of torT and I137_14430 - Song, Li; Tan, Ruimeng; Xiong, Dan; Jiao, Xinan; Pan, Zhiming (Frontiers in Veterinary Science, 2023)
Most cases of chicken salmonellosis are caused by Salmonella enterica serovar Gallinarum biovars Gallinarum and Pullorum, which lead to a significant morbidity and fatality rate. Although the conventional Kaufmann-White scheme is the reliable method for the serotyping of Salmonella, it does not distinguish between closely related biotypes like S. Pullorum and S. Gallinarum. Herein, we conducted a single one-step multiplex PCR assay that can identify and distinguish between S. Pullorum and S. Gallinarum in an accurate manner. This PCR method was based on three genes, including torT for S. Pullorum identification, I137_14430 for S. Gallinarum identification, and stn as the genus-level reference gene for Salmonella. By comparing S. Pullorum to S. Gallinarum and other serovars of Salmonella, in silico study revealed that only the former has a deletion of 126 bp-region in the carboxyl terminus of torT. The I137_14430 gene does not exist in S. Gallinarum. However, it is present in all other Salmonella serotypes. The multiplex PCR approach utilizes unique sets of primers that are intended to specifically target these three different genes. The established PCR method was capable of distinguishing between the biovars Pullorum and Gallinarum from the 29 distinct Salmonella serotypes as well as the 50 distinct pathogens that are not Salmonella, showing excellent specificity and exclusivity. The minimal amount of bacterial cells required for PCR detection was 100 CFU, while the lowest level of genomic DNA required was 27.5 pg/μL for both S. Pullorum and S. Gallinarum. After being implemented on the clinical Salmonella isolates collected from a poultry farm, the PCR test was capable of distinguishing the two biovars Pullorum and Gallinarum from the other Salmonella strains. The findings of the PCR assay were in line with those of the traditional serotyping and biochemical identification methods. This new multiplex PCR could be used as a novel tool to reinforce the clinical diagnosis and differentiation of S. Pullorum and S. Gallinarum, particularly in high-throughput screening situations, providing the opportunity for early screening of infections and, as a result, more effective management of the illness among flocks.